Recent Progress in Enzyme Immobilization to Metal–Organic Frameworks to Enhance the CO2 Conversion Efficiency - Yunhan Cao; Pengyan Yang; Rui Zhao; Fenghuan Wang (Molecules)
Climate change and the energy crisis, driven by excessive CO2 emissions, have emerged as pressing global challenges. The conversion of CO2 into high-value chemicals not only mitigates atmospheric CO2 levels but also optimizes carbon resource utilization. Enzyme-catalyzed carbon technology offers a green and efficient approach to CO2 conversion. However, free enzymes are prone to inactivation and denaturation under reaction conditions, which limit their practical applications. Metal–organic frameworks (MOFs) serve as effective carriers for enzyme immobilization, offering porous crystalline structures that enhance enzyme stability. Moreover, their high specific surface area facilitates strong gas adsorption, making enzyme@MOF composites particularly advantageous for CO2 catalytic conversion. In this paper, we review the synthesis technologies and the application of enzyme@MOFs in CO2 catalytic conversion. Furthermore, the strategies, including the enhancement of CO2 utilization, coenzyme regeneration efficiency, and substrate mass transfer efficiency, are also discussed to further improve the efficiency of enzyme@MOFs in CO2 conversion. The aim of this review is to present innovative ideas for future research and to highlight the potential applications of enzyme@MOFs in achieving efficient CO2 conversion.